UPAYA PELESTARIAN TARI PODANG DI KELURAHAN NAPAR NAGARI KOTO NAN GADANG KECAMATAN PAYAKUMBUH UTARA KOTA PAYAKUMBUH - Gustia Arini E; Desfiarni Desfiarni; Darmawati Darmawati (FBS Universitas Negeri Padang, 2013)
Abstract The Article is aimed to describe the effort done to keep the existence of Podang dance in Napar, Koto Nan Gadang, Payakumbuh utara regency, Payakumbuh town. The data used in this research are primary and secondary data. The techniques of collecting the data are references from the library, observation, interview and documentation. The results are in the form of training carried out toward the youth people in Napar based on the promised and allocated time. It is also found that there is an increasing number of the people joining the training everytime it is carried out : 10 people in the first training, 11 people in the second training and 14 people in the third training. Kata kunci : Pengembangan, Jumlah, Pelaku, Tari, Podang